From Metaphysical Representations to Aesthetic Life : Toward the Encounter with the Other in the Perspective of Daoism. - Lacertosa, Massimiliano (State University of New York Press, 2023)
What is "Chinese philosophy?" What is "philosophy" itself? How can one understand unfamiliar philosophical stances? How can comparison become a prominent philosophical tool? In this book, Massimiliano Lacertosa examines these questions by proposing an ethical understanding of the aesthetic encounter with the other and the world. Through the analysis of the works of Laozi, Zhuangzi, Nietzsche, and Heidegger, among others, this book explores the possibilities of stepping out of the anthropocentric standpoint and seeing the relation of objects in the world under a different light. This implies a shift from the metaphysical representation of the world divided between the sensible and the supersensible to an aesthetic and undivided experience of the world in which one partakes in the constant transformation of the myriad things. Approachable yet rigorous, this book is essential reading for anyone interested in the most fundamental issues of philosophy and in the challenges of doing philosophy in a multicultural context.